Pengaruh Kejenuhan Air Tanah Lempung Organik Menggunakan Permodelan Laboratorium - Makki, Chintia; Setyanto, Setyanto; Afriani, Lusmeilia (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2017)
The limited area for civil construction is affecting people to make building construction upper the clay- organic. The speciment of investigation soil wasobtained in Jabung, East Lampung. The speciment of soil obtaindirect shear and vane shear modeling test usingglass box with contain ±130,730gram/ 130,7kgof soil. Direct shear test for 30 cm depth below surfaceundrained soil obtainsomeresult.The result are forshearing strain is 0,1286 kg/cm2, shearing strain of vane shear test is 0,61 kg/cm2, and the value of bearing capacity is 1,4103 kg/cm2. for 50 cm depth below surfaceundrained soilintoobtain result for shearing strain is 0.1196 kg/cm2, shearing strain of vane shear test is 0,61 kg/cm2, and the value of bearing capacity is 1,7018 kg/cm2. Direct shear test for 30 cm depth below surfacedrained soilobtain result for shearing strain is 0,1286 kg/cm2, shearing strain of vane shear test is 0,61 kg/cm2, and the value of bearing capacity is 1,0347 kg/cm2 , for 50 cm depth below surfacedrained soilobtain result for shearing strain is 0,0861 kg/cm2, shearing strain of vane shear test is 0,46 kg/cm2, and the value of bearing capacity is 1,3997 kg/cm2 From the direct shear and vane shear test, it was obtained that shearingstrain in direct shear test is lower than vane shear test. Keywords: Direct Shear Test, Vane Shear Test, Shearing Strain, The Clay-Organic, Bearing Capacity